Endothelial dysfunction in acute brain injury and the development of cerebral ischemia. Issue 6 (9th February 2015) - van Ierssel, Sabrina H.; Conraads, Viviane M.; Van Craenenbroeck, Emeline M.; Liu, Yin; Maas, Andrew I.R.; Parizel, Paul M.; Hoymans, Vicky Y.; Vrints, Christiaan J.; Jorens, Philippe G.
Abstract : Cerebral ischemia (CeI) is a major complicating event after acute brain injury (ABI) in which endothelial dysfunction is a key player. This study evaluates cellular markers of endothelial function and in vivo reactive hyperemia in patients with ABI and their relationship to the development of cerebral ischemia. We studied cellular markers of endothelial dysfunction and the peripheral reactive hyperemia index (RHI) in 26 patients with ABI at admission and after 6 and 12 days, and compared these with those of healthy volunteers (n = 15). CeI was determined clinically or by computer tomography. In patients with ABI, RHI at admission was significantly reduced compared with healthy subjects ( P  = 0.003), coinciding with a decrease in circulating endothelial progenitor cells (EPC; P  = 0.002). The RHI recovered in eight patients without development of CeI, but failed to fully recover by day 12 in three of four patients who developed CeI. Despite recovery of the RHI within 12 days in these patients ( P  = 0.003), EPC count remained significantly lower after 12 days in patients with ABI ( P  = 0.022). CD31 + T cells and endothelial microparticles were not different between controls and patients. No differences were noted in cellular markers of endothelial dysfunction in patients developing CeI and those not. In conclusion, patients with ABI exhibit impaired microvascular endothelial function measured as RHI and a decreased circulating level of EPC. © 2015 Wiley Periodicals, Inc.